Melatonin antagonizes cadmium‐induced neurotoxicity by activating the transcription factor EB‐dependent autophagy–lysosome machinery in mouse neuroblastoma cells. Issue 3 (3rd August 2016) - Li, Min; Pi, Huifeng; Yang, Zhiqi; Reiter, Russel J.; Xu, Shangcheng; Chen, Xiaowei; Chen, Chunhai; Zhang, Lei; Yang, Min; Li, Yuming; Guo, Pan; Li, Gaoming; et al.
Abstract: Cadmium (Cd), a highly ubiquitous heavy metal, induces neurotoxicity. Melatonin, a major secretory product of the pineal gland, protects against Cd‐induced neurotoxicity. However, the mechanism that accounts for this protection remains to be elucidated. Herein, we exposed mouse neuroblastoma cells (Neuro‐2a cells) to different concentrations of cadmium chloride (CdCl2 ) (12.5, 25, and 50 μ mol L −1 ) for 24 hours. We showed that Cd inhibits autophagosome–lysosome fusion and impairs lysosomal function, subsequently leading to nerve cell death. In addition, Cd decreases the level of transcription factor EB (TFEB) but induces the nuclear translocation of TFEB, associated with compromised lysosomal function or a compensatory effect after the impairment of the autophagic flux. Moreover, compared to the 50‐μ mol L −1 Cd group, administration of 1 μ mol L −1 melatonin increased "TFEB‐responsive genes" ( P <.05) and the levels of lysosomal‐associated membrane protein (0.57±0.06 vs 1.00±0.11, P <.05), preserved lysosomal protease activity (0.52±0.01 vs 0.90±0.02, P <.05), maintained the lysosomal pH level (0.50±0.01 vs 0.87±0.05, P <.01), and enhanced autophagosome–lysosome fusion (0.05±0.00 vs 0.21±0.01, P <.01). Notably, melatonin enhanced TFEB expression (0.37±0.04 vs 0.72±0.07, P <.05) and nuclear translocation (2.81±0.08 vs 3.82±0.05, P <.05). Tfeb siRNA blocked the melatonin‐mediated elevation in autophagy–lysosome machinery in Cd‐induced neurotoxicity ( P <.01). Taken together, these results uncover a potent role for TFEB‐mediated autophagy in the pathogenesis of Cd‐induced neurotoxicity, suggesting that control of the autophagic pathway by melatonin might provide an important clue for exploring potential targets for novel therapeutics of Cd‐induced neurotoxicity.